ANALISIS PELAN INDUK PEMBANGUNAN PENDIDIKAN (PIPP) 2006-2010 DIGUBAL BERDASARKAN PEMBANGUNAN PENDIDIKAN MALAYSIA (2001-2010) - Shahril @ Charil Hj Marzuki; Norfizah Hayati Ahmad; Muhammad Faizal A. Gani (Jurnal Internasional Manajemen Pendidikan, 2010)
This article examines and analyzes critically the National  Education Blueprint (NEB) (PIPP) (2006- 2010) which has six main trusts: (i) building the nation and people that is united and pround of its national identity, (ii) developing human capital that is knowledgeable and skilled with  an appreciation of pure values, (iii) strengthening national  schools, making national schools the main choice without obstructing the development of vernacular schools, (iv) narrowing the education gap in term of location, socio-economic status and students abilities so that all schools and students will be given the same opportunities to achieve exellence, (v) improving teaching profession, and (vi) accelerating excellence at educational institution, through cluster schools (which are centres of excellence) so that they will become showcase or model schools.Whether  the NEB had been formulated based on Vision 2020, which have  nine main strategies, the Education Development Plan ( 2001- 2010 ) which  has four main thrusts, namely  (i) increase acess in education, (ii) increase equity in education, (iii) improve quality in education, and (iv) improve efficiency and effectiveness of education management and whilst the Ninth  Malaysia Plan which has six core strategies namely (i) improveing the access to and quality of the education system at all levels, (ii) making national schools the school of choice, (iii) Producing tertiary institution of international standing, (iv) nurturing top quality research and development and scientific and innovation, and (v) Empowering women and youth and (vi) fostering a society with strong values. It is  also discussed the issues and implementation  of NEB.